Metrics for evaluating the ecological benefits of decreased nitrogen deposition. (August 2017) - Rowe, E.C.; Jones, L.; Dise, N.B.; Evans, C.D.; Mills, G.; Hall, J.; Stevens, C.J.; Mitchell, R.J.; Field, C.; Caporn, S.J.M.; Helliwell, R.C.; Britton, A.J.; et al.
Abstract: Atmospheric pollution by reactive nitrogen (N) can have profound effects on ecosystem functioning and biodiversity. Numerous mechanisms are involved, and response times vary among habitats and species. This complex picture can make it difficult to convey the benefits of controlling N pollution to policy developers and the public. In this study we evaluate pressure, midpoint, and endpoint metrics for N pollution, considering those currently in use and proposing some improved metrics. Pressure metrics that use the concept of a critical load (CL) are useful, and we propose a new integrated measure of cumulative exposure above the CL that allows for different response times in different habitats. Biodiversity endpoint metrics depend greatly on societal values and priorities and so are inevitably somewhat subjective. Species richness is readily understood, but biodiversity metrics based on habitat suitability for particular taxa may better reflect the priorities of nature conservation specialists. Midpoint metrics indicate progress towards desired endpoints – the most promising are those based on empirical evidence. Moss tissue N enrichment is responsive to lower N deposition rates, and we propose a new Moss Enrichment Index (MEI) based on species-specific ranges of tissue N content. At higher N deposition rates, mineral N leaching is an appropriate midpoint indicator. Biogeochemical models can also be used to derive midpoint metrics which illustrate the large variation in potential response times among ecosystem components. Metrics have an important role in encouraging progress towards reducing pollution, and need to be chosen accordingly. Graphical abstract: Highlights: Metrics are important for communicating progress in decreasing nitrogen (N) pollution. We evaluate pressure, midpoint, and endpoint metrics for N pollution. We propose new pressure metrics based on recent deposition above the critical load. Moss tissue N, and N leaching, are good midpoints at low, and high, N deposition. Biodiversity endpoints need to reflect societal values as well as natural science.